Qualitative analysis of elite football players` causal attribution to not playing: A perspective of attribution theory - Ulas, M.; Adilogullari, I.; Senel, E. (PLOS ONE, 2025)
This study explores the causal attributions of professional football players who experience reduced playing time or exclusion from the squad, focusing on the psychological and relational consequences of these experiences. Using a qualitative thematic analysis approach, semi-structured interviews were conducted with 16 elite football players from Turkey`s top league, all of whom had represented the national team. The findings reveal that players predominantly attribute their exclusion to coach preferences and subjective decisions, rather than their performance. This attribution process often leads to negative emotional outcomes, including feelings of exclusion, loss of motivation, diminished self-worth, and identity confusion. The study also highlights that a lack of clear communication from coaches exacerbates these negative emotions and can strain both team dynamics and players` personal lives. Furthermore, the results indicate that prolonged periods of exclusion may result in decreased training effort and a decline in overall performance, creating a negative feedback loop. These findings underscore the importance of transparent communication and supportive coach-athlete relationships in mitigating the adverse effects of reduced playing time. The study contributes to the literature by providing new insights into the underexplored area of athletes` psychological responses to exclusion and offers practical recommendations for coaches to foster athlete motivation and well-being, even in challenging circumstances.